PENGARUH LEVERAGE, SIZE, LIKUIDITAS, ARUS KAS OPERASI TERHADAP REVALUASI ASET TETAP - Dian Firmansyah; Nurmala Ahmar; Jmv Mulyadi (Jurnal Ilmiah Manajemen dan Bisnis, 2017)
The aim of this study are to prove empirically the effect of leverage, size, liquidity andoperating cash flows of the fixed asset revaluation. The research is using sample from allnon financial companies, which doing revaluation asset during 2012-2015 throughregistered company in Indonesian Stock Exchange by upward revaluation category. Thisresearch is using Path analysis (PLS) without requiring the classical assumption test andnormality. The results showed that the leverage effect on the revaluation of fixedassets, itis proved that high leverage is reason for the company to decided doing the revaluation offixed assets, the large company is tend want to show decrease the earnings report toreduce the political cost, assets revaluation would caused recalculate value ofdepreciation to increase expense and to reduce company profits. Cash flow operationaffected the revaluation of fixed assets to company needs to be able to paid obligationsand assets revaluations required a large fund for appraisal services, audit fee and taxfinal payment. Whereas, for the liquidity is found did not effect to fixed asset revaluation,hight cost to assets revaluation and low liquidity is not reason for the company to choosethe revaluation model. In during four years of research found that the asset revaluationmodel which reported in Other comprehensive income is growing and expected to makethe financial report advantages and high quality increase through reported by fair valuein the financial report.